The Sulfated Triphenyl Methane Derivative Acid Fuchsin is a Potent Inhibitor of Amyloid Formation by Human Islet Amyloid Polypeptide and Protects Against the Toxic Effects of Amyloid Formation - Meng, Fanling (2010)
Islet amyloid polypeptide (IAPP), also known as amylin, is responsible for amyloid formation in type 2 diabetes. The formation of islet amyloid is believed to contribute to the pathology of the disease by killing β-cells and it may also contribute to islet transplant failure. The design of inhibitors of amyloid formation is an active area of research, but comparatively little attention has been paid to inhibitors of IAPP in contrast to the large body of work on Aβ and most small molecule inhibitors of IAPP amyloid are generally effective only when used at a significant molar excess. Here we show that the simple sulphonated triphenyl methane derivative acid fuchsin, (3-(1-(4-Amino-3-methyl-5-sulphonatophenyl)-1-(4-amino-3-sulphonatophenyl) methylene) cyclohexa-1,4-dienesulphonic acid), is a potent inhibitor of in vitro amyloid formation by IAPP at substoichiometric levels and protects cultured rat INS-1 cells against the toxic effects of human IAPP. Fluorescence detected thioflavin-T binding assays, light scattering, circular dichroism, two dimensional IR and TEM measurements confirm that the compound prevents amyloid fibril formation. Ionic strength dependent studies show that the effects are mediated in part by electrostatic interactions. Experiments in which the compound is added at different time points during the lag phase of amyloid formation have commenced reveal that it arrests amyloid formation by trapping intermediate species. The compound is less effective against the Aβ peptide, indicating specificity in its ability to inhibit amyloid formation by IAPP. The work reported here provides a new structural class of IAPP amyloid inhibitors and demonstrates the power of two-dimensional IR for characterizing amyloid inhibitor interactions.